Complaint Authority for Constitutional Complaint by Indonesia’s Constitutional Court - Sri Warjiyati; Kayode Muhammed Ibrahim; Safrin Salam; Umar Faruq (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Constitutional Court will be able to provide protection for constitutional rights which will produce institutions that are able to provide answers to reforms. The presence of the Constitutional Court third amendment to the 1945 Constitution of the Republic of Indonesia, which became the basis of Article 24C. The legitimacy of the Constitutional Court in a limited way is formulated, namely: to begin, to investigate legislation that violates the constitution, to adjudicate disputes over the power of state institutions vested with constitutional authority, and to adjudicate the dissolution of political parties and settlement, the four general election disputes. In the modern state administration discourse, it currently requires the Constitutional Court to expand the scope of its authority in relation to Constitutional Complaints or commonly referred to as Constitutional Complaints. The necessity of one of these powers can be seen in the number of state institutions that violate the constitutional rights of citizens through the actions of these institutions. However, the channel for this complaint still does not exist, only that currently exists in providing protection for the right of Constitutional Complaints to be protected through judicial review of the basic constitution as regulated in the constitution.